2021
DOI: 10.1186/s12931-021-01661-8
|View full text |Cite
|
Sign up to set email alerts
|

Beta-blocker therapy in patients with COPD: a systematic literature review and meta-analysis with multiple treatment comparison

Abstract: Background Beta-blockers are associated with reduced mortality in patients with cardiovascular disease but are often under prescribed in those with concomitant COPD, due to concerns regarding respiratory side-effects. We investigated the effects of beta-blockers on outcomes in patients with COPD and explored within-class differences between different agents. Methods We searched the Cochrane Central Register of Controlled Trials, Embase, Cumulative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 67 publications
0
17
0
Order By: Relevance
“…Other observational studies report reduced mortality, and a recent meta-analysis concludes a general tendency towards reduced risk of mortality. 15 Differing results might depend on study population factors, such as disease severity and treatment, with both Ekström et al 27 and the present study primarily including patients with advanced COPD. Furthermore, differences in study design, including adjustment for immortal time bias, may very well explain differing results, as immortal time bias often leads to intervention risk reduction in pharmacoepidemiologic studies.…”
Section: Beta-blocker Use and Mortalitymentioning
confidence: 76%
See 2 more Smart Citations
“…Other observational studies report reduced mortality, and a recent meta-analysis concludes a general tendency towards reduced risk of mortality. 15 Differing results might depend on study population factors, such as disease severity and treatment, with both Ekström et al 27 and the present study primarily including patients with advanced COPD. Furthermore, differences in study design, including adjustment for immortal time bias, may very well explain differing results, as immortal time bias often leads to intervention risk reduction in pharmacoepidemiologic studies.…”
Section: Beta-blocker Use and Mortalitymentioning
confidence: 76%
“…The present study, and the lack of association found between beta-blocker use and AECOPD risk, is in discordance with previous meta-analyses and observational studies reporting an association between use of beta-blockers and a reduced risk of exacerbations. 15,24 The nationwide Danish publication by Rasmussen et al 25 reported an association between beta-blocker use and reduced risk of exacerbations in COPD patients following hospitalization with a diagnosis of AMI. In contrast, the RCT BLOCK COPD 13 included patients without CVD and reported an increased risk of severe AECOPD (but not time to exacerbation) in beta-blocker users.…”
Section: Beta-blocker Use and Exacerbationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Those with asthma-HFrEF had 43% less chance of being prescribed a beta-blocker compared with patients with HF-alone. Current guidelines recommend that asthma patients with chronic HFrEF should not receive disease-modifying beta-blocker treatment due to possible bronchoconstriction, despite evidence to suggest that cardioselective beta-blockade may be used with careful up-titration and monitoring,30 31 where benefits may outweigh risks in individual patients. Based on the low uptake across the whole spectrum of HF medications in patients with additional lung disease (figure 3), we expect these patients would have worse prognosis compared with their more adequately treated counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…26 However, an analysis of linked data from the UK Clinical Practice Research Datalink found that cardioselective BBs, unlike nonselective BBs, were not associated with the risk of moderate or severe exacerbation of asthma in patients with cardiovascular disease and comorbid asthma. 27 Furthermore, in a systematic review and multiple treatment comparison meta-analysis of 23 observational studies and 14 RCTs, Gulea et al 28 found that only propranolol was associated with reduced forced expiratory volume during the first second (FEV1); otherwise, relative to no treatment, BB treatment was actually associated with a reduced risk of acute exacerbation of chronic obstructive pulmonary disease events (hazard ratio, 0.77; 95% CI, 0.70-0.85). A qualitative analysis of the data in this study suggested no detrimental effect of BBs on quality of life, all-cause hospitalization, and mortality outcomes.…”
Section: Parting Notes: β-Blockers and Bronchoconstrictionmentioning
confidence: 99%